IMPLEMENTASI KEBIJAKAN RENCANA TATA RUANG WILAYAH KABUPATEN JENEPONTO - Hijrah Lail; Hasrat Arief Saleh; Atta Irene Allorante (Program Studi Administrasi Publik, 2020)
The Implementation of Spatial Planning policy is one of the producst of the local government in city planning field. The research aims to analyze the implementation of the spatial planning policy in Jeneponto Regency. This research used qualitative approach and the data were collected through observation, interview, and documen tation. Data analysis technique consisted of processing the data, buiding general sense, and coding the data. The research result indicate that the implementation of spatial planning has not been optimumdue to: problems in communication, human resources, disposition, and bureacratic structure. Since Jeneponto Regency is still in developing stage, it is still easier to implement the policy and this becomes the supporting factor. Whereas, the inhibiting factor is the lack of similar vision among the stakeholders about the importance of spatial plan, including the SKPD in the local government that has been actively participated in implementing the spatial planning.